Case report: Eighteen nails gun shots in the head, thorax and abdomen but still conscious at admission: A challenging patient for the cardiac surgeon! - Ouda, Ahmed; Schürner, Anna Maria; Schmiady, Martin Oliver; Jukema, Gerrolt Nico; Vogt, Paul Robert; Carrel, Thierry (Frontiers in Cardiovascular Medicine, 2023)
We report an unusual case of multiple penetrating cerebral, cardiac and abdominal injuries following a suicidal attempt using a nail gun. Successful treatment required several emergency procedures and resulted from a wise interdisciplinary management and timing of surgery.